MODEL PENGELOLAAN KELAS DALAM PEMBELAJARAN PAI DI SD RIYADLUL ARKHAM TEMBONG PLINTAHAN PANDAAN - M. Anang Sholikhudin Halimatus Sa’diyah (Universitas Yudharta Pasuruan, 2017)
Today KBM can not only be done in the classroom. In addition, the learning system is monotonous. This can lead to saturation of the students, so that the learning process is not conducive to the understanding of students in a lesson. KBM can also be implemented outside the school building, for example: in the garden courtyard of the school, library, or any place that could be used KBM.This study aims to determine how the implementation of classroom management in learning PAI in SD Riyadlul Arkham Tembong Plintahan Pandaan. And what are the factors supporting and hindering the implementation of classroom management model in PAI learning in primary Riyadlul Tembong Arkham Plintahan Pandaan.This study is a qualitative research, with a shot in SD Riyadlul Arkham Tembong Plintahan Pandaan. The subject of research aadalah PAI Teachers and students of elementary Riyadlul Arkham Tembong Plintahan Pandaan. Data was collected by using observation, interview, and documentation. The analysis of the data used is data collection, data reduction, data presentation, drawing conclusions.The results showed that: the implementation of classroom management in learning PAI in SD Riyadlul Arkham there are two kinds, the first can improve the learning outcomes of this is due to the ability of teachers and learning media has been good, the second is the lack of enthusiasm of learners in the learning of this is due to the apathy of learners against teachers.The conclusion of this study is the first, there is an increase learning outcomes for teachers to implement classroom management in learning PAI in SD Riyadlul Arkham Tembong Plintahan Pandaan. Second, the major contributing factor in the learning management implementation class in elementary Riyadlul Arkham PAI is the availability of teachers and adequate learning device. While the inhibiting factors of the implementation of classroom management in learning in primary Riyadlul Arkham PAI is the lack of enthusiasm of students to teachers felt it was understood due to the lesson.